2019
DOI: 10.12965/jer.1938362.181
|View full text |Cite
|
Sign up to set email alerts
|

The effects of home-based stair and normal walking exercises on lower extremity functional ability, fall risk factors, and cardiovascular health risk factors in middle-aged older women

Abstract: The purpose of this study was to exam 12 weeks of stair and normal walking effects on lower extremity functional ability and cardiovascular health risk factors in middle-aged older women. Twenty-four subjects were assigned either to the stair walking group (SWG, 57.40±6.11 years, n=10) or the normal walking group (NWG, 57.28±16.83 years, n= 14). They performed exercises 3 times per week, 60 min per day for 12 weeks. Lower extremity functional ability (lower extremity muscular strength, walking speed, active an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
0
5
0
7
Order By: Relevance
“…Matos et al, [16] with 12 weeks of HIIT reported improvements of 15.1% in TC, 24.3% in TG and 7% in GL and refer that two session a week are feasible and effective to induce relevant improvements in older women. Kang et al, [27] with 12 weeks of aerobic exercise obtained 8.8% in TC, 34.4% in TG and 5% in GL. In a seven-year study with aerobic exercise Zajac-Gawlak, et al [28] observed 16.6% and 9.4% improvement in TG and GL, respectively, referring that increases in daily steps/day is related to a lower risk of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Matos et al, [16] with 12 weeks of HIIT reported improvements of 15.1% in TC, 24.3% in TG and 7% in GL and refer that two session a week are feasible and effective to induce relevant improvements in older women. Kang et al, [27] with 12 weeks of aerobic exercise obtained 8.8% in TC, 34.4% in TG and 5% in GL. In a seven-year study with aerobic exercise Zajac-Gawlak, et al [28] observed 16.6% and 9.4% improvement in TG and GL, respectively, referring that increases in daily steps/day is related to a lower risk of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 91%
“…Our lipidic improvement can be explained from the combined type of exercise of ME. Regular aerobic exercise promotes improvements in TC, TG and GL [21,25,27,30] and enhances oxidative enzymes that are associated to better insulin sensitivity [30]. RT training is also powerful for changing the level of lipoproteins [20], to improve the decline in myosin chain and increase protein synthesis rate leading to enhanced glucose oxidation and a better insulin sensitivity, and to improve metabolic biomarkers in elderly women but are depended on volume, intensity and initial level of the subjects, since participants with higher GL and TG values can obtain better results [21,22,30].…”
Section: Discussionmentioning
confidence: 99%
“…On the start signal, the participants were then instructed to stand up completely and sit down, which was measured as 1 count, and to repeat this as many times as possible. The number of repetitions completed in 30 s was recorded [36,37].…”
Section: Fall-related Fitness 2241 Thirty-seconds Sit To Stand Testmentioning
confidence: 99%
“…Even though various types of exercise, such as strengthening, endurance and exibility are can be performed for the elderly [11], cycling, walking and other exercise at home have been recommended [12]. Some reports indicated that communityhome exercise either indoor or outdoor walking is a simple and easy program for improving quality of life in either elderly participants or patients with arterial disease [13][14][15]. However, the intensity of walking should be not too heavy, as that may increase oxidative stress.…”
Section: Introductionmentioning
confidence: 99%